2016
DOI: 10.4028/www.scientific.net/kem.697.7
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Sintering of Transparent Aluminum Oxynitride (AlON) Ceramics Using MgO and Y<sub>2</sub>O<sub>3</sub> as Co-Additives

Abstract: Transparent aluminum oxynitride (AlON) ceramics have been prepared through a method based on direct reaction sintering of alumina and aluminum nitride powders using MgO and Y2O3 as co-additives. The sintering additives could cause the formation of liquid phase during sintering, which would greatly promote the densification and eliminate pores. The grain size of AlON is about 50-100μm. The influence of different component of Al2O3 and AlN as well as sintering temperature on microstructure and optical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The trend shown by these parameters was similar to that shown by the transmittance of the ceramics (Figure 3(A)). To our surprise, the ceramic doped with 0.1 wt.% Y 2 O 3 ‐0.4 wt.% MgAl 2 O 4 ‐0.12 wt.% H 3 BO 3 showed a haze as low as 3.46% and an in‐line transmittance of up to 81% at 600 nm, which is much higher than those of the reactive sintered AlON ceramics previously reported 7‐9 . A comparison of the optical performance of the one‐step reactive sintered ceramics prepared in this study with those of the previously reported data (Figure 3(B)) revealed that a breakthrough in this study has been achieved in terms of the thickness and transmittance.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…The trend shown by these parameters was similar to that shown by the transmittance of the ceramics (Figure 3(A)). To our surprise, the ceramic doped with 0.1 wt.% Y 2 O 3 ‐0.4 wt.% MgAl 2 O 4 ‐0.12 wt.% H 3 BO 3 showed a haze as low as 3.46% and an in‐line transmittance of up to 81% at 600 nm, which is much higher than those of the reactive sintered AlON ceramics previously reported 7‐9 . A comparison of the optical performance of the one‐step reactive sintered ceramics prepared in this study with those of the previously reported data (Figure 3(B)) revealed that a breakthrough in this study has been achieved in terms of the thickness and transmittance.…”
Section: Resultssupporting
confidence: 53%
“…(A) Transmittance of the AlON ceramics with 0.1 wt.% Y 2 O 3 ‐0.4 wt.% MgAl 2 O 4 ‐ x wt.%H 3 BO 3 ; (B) comparison of the transmittance of the AlON ceramics prepared by one‐step reactive sintering 7‐9 [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the addition of sintering aids, which are rare‐earth metallic oxides, such as Y 2 O 3 /La 2 O 3 , and alkaline earth metallic oxides, such as MgO, is an important factor that affects the properties of AlON ceramics 14–18 . However, a single type of sintering aid is insufficient to meet the performance requirements of AlON ceramics; therefore, composite sintering aids have become popular.…”
Section: Introductionmentioning
confidence: 99%